Intellectual capital and knowledge management at the national university of San Marcos (2008-2010) - Ramirez Miranda, Durga Edelmira (2011)
The main objective of the study is to determine the relationship between Intellectual Capital Knowledge Management mainly in the area of teaching and research at the Universidad National Mayor de San Marcos 2008-2010. To achieve the objective were used for analysis and synthesis methods and technique was applied to a sample survey of 100 professors of engineering and social sciences faculties and interviewed experts. The results indicate that the intellectual capital within the framework of knowledge management in universities is a matter of great importance as an essential resource for innovation and competitiveness and productivity demands imposed by the dynamics of the globalized world is not no substantive relationship between human capital, structural capital and relational capital in college, which is why there is greater productivity in innovation, research and development (IDI).